Pengaruh Promosi dan Kualitas Layanan terhadap Minat Masyarakat Membayar Zakat - Erdani Murdani Nur (STAI Auliaurrasyidin Tembilahan, 2020)
Zakat is one of the pillars of Islam that every capable Muslim must do. One of the institutions that manage zakat funds is the National Zakat Agency (BAZNAS). This study aims to partially and simultaneously examine the effect of promotion and service quality on people's interest in paying zakat through BAZNAS, Indragiri Hilir Regency. This type of research is field research. The data used in this study were primary and secondary. 87 Respondents in this study were Muzakki in BAZNAS Indragiri Hilir Regency. The sampling technique used was simple random sampling. The data collection methods were questionnaires, interviews, and documentation. The data analysis technique partially used the t-test and simultaneously used the Anova test. The results showed that either partially or simultaneously, promotion and service quality had a significant influence on people's interest in paying zakat in BAZNAS, Indragiri Hilir Regency.